2011
DOI: 10.1093/infdis/jir032
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response Effect of Incarceration Events on Nonadherence to HIV Antiretroviral Therapy Among Injection Drug Users

Abstract: Among HIV-seropositive IDUs receiving ART, an increasing burden of incarceration was associated with poorer adherence in a dose-dependent fashion. Our findings support improved adherence support for HIV-seropositive IDUs experiencing incarceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
129
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 38 publications
11
129
0
Order By: Relevance
“…This highlights the critical need to improve adherence in criminal justice settings. 38,39 Thus, our study supports the provision of increased and improved support for ART adherence among these younger drug users, those in the sex trade and the recently incarcerated, to reduce the risk of viral rebound.…”
Section: Discussionsupporting
confidence: 65%
“…This highlights the critical need to improve adherence in criminal justice settings. 38,39 Thus, our study supports the provision of increased and improved support for ART adherence among these younger drug users, those in the sex trade and the recently incarcerated, to reduce the risk of viral rebound.…”
Section: Discussionsupporting
confidence: 65%
“…19,20 Adherence and maintenance of routine engagement in medical services is often a struggle for HIV-positive individuals after release from incarceration, due in large part to the fact that a history of incarceration itself can be a barrier to adhering to HIV antiretroviral medications. 21 For instance, among injection drug users, Milloy and colleagues 21 found that HIV-positive individuals with a history of incarceration had nearly double the odds of anti-retroviral adherence lapse.…”
Section: Introductionmentioning
confidence: 99%
“…These linkages are critical to maintaining continuance of ART after release given incarceration and subsequent release have been associated with virologic failure. [18][19][20] Social work and case management support is also an important component to successful transitional care. We found that 58% of newly diagnosed persons linked to care at the Miriam Hospital at some point through 2009, but only 12.5% linked within 90 days of the index incarceration in a system that had co-located physicians and dedicated case management services for HIV-infected prisoners being released to the community.…”
Section: Discussionmentioning
confidence: 99%